Kompensasi dan Budaya Organisasi Terhadap Turnover pada PT. BPR Gunung Slamet Cilacap - Selindha Rosanti Pramono; Puspita Wulansari (IPM2KPE, 2023)
The purpose of this study is to ascertain how compensation and organizational culture at PT. BPR Gunung Slamet Cilacap affect turnover. This study used a quantitative methodology that included multiple linear regression analysis and descriptive analysis approaches. According to the study's findings, the combined impact of organizational culture and compensation on turnover are known to be 51.2%, with other factors influencing the remaining 48.8%. Conclusion: Both salary and organizational culture have a considerable impact on the turnover variable, though not equally. salary has a significant positive impact on turnover, whereas organizational culture has an enormous adverse influence. Keywords: Organizational Culture, Compensation, Turnover